2012
DOI: 10.1590/s0006-87052012005000036
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and path analysis in components of fiber yield in cultivars of upland cotton

Abstract: This study evaluated the relative contribution of agronomic and technological components on the fiber yield in upland cotton cultivars. The experiment was carried out with 11 upland cotton cultivars in a completely randomized blocks design with three replications. Initially, we performed analysis of variance, with the F test at 5% probability for the effect of cultivar as fixed effects as well as block and environment effects as random. Then the values were ordered according to cluster test Scott-Knott, at 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This information is important for cotton breeding programs aimed at selecting genotypes with longer fiber length, since an indirect selection will improve other important traits for fiber processing. Similar results were observed by Ulloa (2006), Hoogerheide et al (2007), Araújo, Almeida, Bertini, Vidal Neto, and Bleicher (2012), Farias, Carvalho, Silva Filho, and Teodoro (2016 a and b) and Queiroz et al (2017b), which verifies the importance of selecting cotton genotypes with higher UHM.…”
Section: Phenotypic Correlationssupporting
confidence: 83%
“…This information is important for cotton breeding programs aimed at selecting genotypes with longer fiber length, since an indirect selection will improve other important traits for fiber processing. Similar results were observed by Ulloa (2006), Hoogerheide et al (2007), Araújo, Almeida, Bertini, Vidal Neto, and Bleicher (2012), Farias, Carvalho, Silva Filho, and Teodoro (2016 a and b) and Queiroz et al (2017b), which verifies the importance of selecting cotton genotypes with higher UHM.…”
Section: Phenotypic Correlationssupporting
confidence: 83%
“…The coefficient of variation (CV) has been used by researchers to describe the accuracy of their experiments (DinardoMiranda and Fracasso 2010; Araújo et al 2012;Granato et al 2014), since it gives a general indication of the variation levels using the standard deviation as a fraction of the mean (Arnhold andMilani 2011). Consequently, Pimentel-Gomes (1985) conducted a classification of the CVs obtained from agricultural studies, which were classified as low for values lower than 10%, moderate for values from 10 to 20%, high for values higher than 20 up to 30% and very high for values higher than 30%.…”
Section: Introductionmentioning
confidence: 99%
“…Kampli et al, 2002, reported high GCV and PCV for some yield characters. While Arauja et al, 2012, reported that the lowest GCV and PCV values were associated with fiber quality characters is due to the smaller number of genes influencing their responses.…”
Section: The Comparison Of Mean and Range Of Expression Of Different ...mentioning
confidence: 98%